Influência do período pós-colheita das hastes de critrus, sobre a qualidade das borbulhas para a enxertia - Lopes Teixeira, Sílvio; Lopes Teixeira, Sílvio; Andersen, Otto; Roscoe Cardinalli, Lúcio (Revista Ceres, 2025)
This study was made to test the influence of the length of the storage period of the Citrus budwood on the quality of buds for grafting. This work was conducted at the Instituto de Pesquisa e Experimentação Agropecuárias do Centro-Oeste, in Sete Lagoas, Minas Gerais State.